ENTREVISTA CON LAURENCE VIENNOT - CAROLINA MARIN (Universidad Distrital Francisco José de Caldas, 2010)
Interview with Laurence Viennot. Brief Biography: Laurence Viennot, born in France. She conducted research in the astrophysics field, in Paris, from 1970 until 1975. In 1977, she obtained her PhD in physics education at the University Denis Diderot, Paris VII. In this University she founded and directed the master's program in Science Education, and, worked alternately as a professor in the Department of Physics. She researched and wrote important works about common knowledge and reasoning ways in learning physics.Questions for Professor Viennot: 1. What are you doing currently in physics teaching research?. 2. What is your opinion about the emerging of science education research, and inside it, the physics didactic as an autonomous field of research? 3. What do you consider is the most important knowledge to teach to future physics teachers? 4. How do you suggest to include issues of modern physics in physics education,at the secondary level? 5. Why there is a need research on natural reasoning in physics? 6. What that's mean "common reasoning" in physics? 7. Can you talk us about physics texts that, usually have the laws, concepts and physical phenomena in a very "simplistic" or general? 8. How influential can become textbooks on reasoning ways in physics learning? 9. What is the teacher's role in the analysis of such texts? 10. You said that in France the content and teaching texts evolved, how did this change? What was the proposal to publishers? 11. How to contribute to systemic analysis beyond the ritual practices? 12. What factors should be taken into account to contribute in improvement of teaching and learning processes in physics class? 13. What do you think about Colombia, and your experience in this academic event?